Operations Management: Sustainability and Supply Chain Management, Global Edition - Heizer, Jay; Render, Barry; Munson, Chuck (Pearson International Content, 2023)
Operations Management: Sustainability and Supply Chain Management presents a broad introduction to the field of operations in a practical and application-oriented manner. Through detailed behind-the-scenes perspectives on the production of goods and services—from music concerts to e-commerce package delivery, manufacturing an aircraft to 3D printed stakes—this text offers an inside view that helps students gain a true understanding of how operations work within an organization. This 14th Edition addresses current trends and practices in operations management, including Industry 4.0 (also known as the Fourth Industrial Revolution), which is transforming the automation, monitoring, and analysis of supply chains through smart technology; and COVID-19 and its impact on global supply chains. The resources help you better understand concepts important to today's operations management professionals.